East African Hip Hop: Youth Culture and Globalization. Mwenda Ntarangwi. Urbana and Chicago: University of Illinois Press. 2009. 158 pp. ISBN: 978-0-252-076534 pb; 978-0-252-03457-2 hb. - Sanga, Imani (International Library of African Music, 2010)
pages: 139-141
Keywords: African Music